Immobilized Rhizopus oryzae lipase catalyzed synthesis of palm stearin and cetyl alcohol wax esters: Optimization by Response Surface Methodology - Sellami, Mohamed (BioMed Central, 2011)
BACKGROUND: Waxes are esters of long-chain fatty acids and long-chain alcohols. Their principal natural sources are animals (sperm whale oil) and vegetables (jojoba) which are expensive and not easily available. Wax esters synthesized by enzymatic transesterification, using palm stearin as raw material, can be considered as an alternative to natural ones. RESULTS: Palm stearin is a solid fraction obtained by fractionation of palm oil. Palm stearin was esterified with cetyl alcohol to produce a mixture of wax esters. A non-commercial immobilized lipase from Rhizopus oryzae was used as biocatalyst. Response surface methodology was employed to determine the effects of the temperature (30-50°C), the enzyme concentration (33.34-300 IU/mL), the alcohol/palm stearin molar ratio (3-7 mol/mol) and the substrate concentration (0.06-0.34 g/mL) on the conversion yield of palm stearin. Under optimal conditions (temperature, 30°C; enzyme concentration, 300 IU/mL; molar ratio 3 and substrate concentration 0.21 g/mL) a high conversion yield of 98.52% was reached within a reaction time of 2 h. CONCLUSIONS: Response surface methodology was successfully applied to determine the optimum operational conditions for synthesis of palm stearin based wax esters. This study may provide useful tools to develop economical and efficient processes for the synthesis of wax esters.